(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The study Carried out in the western part of Babylon Province , midst Iraq inside , located between latitude 32º 04′27″.40 to32º41′09″.53 N and longitude 44º08′22″.35 to 44º 56′59″.58 E . This study is conducted to Spatial predicted for Salinity, Sodium adsorption ratio and Groundwater suitable to irrigation by through the application of Spherical Model predicted an accurate 0.9993**, 0.9996** and 0.9944** each of respectively, in addition to diagnosis of salinity, the Sodium Adsorption Ratio and Exchangeable Sodium Percentage in the soil by Vegetation Indices using Soil-Adjusted Vegetation Index, Optimized Soil-Adjusted Vegetation Index(OSAVI) and Generalized Difference Vegetation Index(GDVI2) an accurate 0.9919**, 0.9927** and 0.9878** each of respectively . Furthermore the maps showed spatial fitting and highly significant correlation between Salinity, Sodium Adsorption Ratio and Exchangeable Sodium percentage of soil with Salinity, Sodium Adsorption Ratio and Groundwater suitable to irrigation